Orchids of the Principality of Asturias (Northwestern Spain) - González-García, Víctor; Argüelles Longo, Ángel; Carlón, Luis (Mediterranean Botany, 2025)
In this study we present a review of the orchid family in the Principality of Asturias, Northwestern Spain. The study area comprises 10,000 km² for which we have compiled and curated up to 9197 records coming from several sources: fieldwork, herbaria, specialized publications, gray-literature, citizen science platforms, Global Biodiversity Information Facility (GBIF) and social media. The territory comprises 52 confirmed species and 13 hybrids, with other 16 possibly present species being discussed and still other 6 explicitly dismissed. Gymnadenia densiflora (Wahlenb.) A. Dietr. and all nothotaxa, except those in Serapias, represent novelties for the area. For each of the 52 species we provide a brief description of their habitat, altitudinal range and flowering period. Additionally, we present a statistical exploration of the main drivers of orchids’ ecology and distribution in the territory. Our review demonstrates how the Principality of Asturias, despite its marginal geographic position—away from major diversification centers—, and the scarcity of detailed floristic studies and, in particular, of those specifically focused on orchids, qualifies as a significantly orchid-rich region within the European context, even when judged by the demanding standards of the rich Iberian flora. The role of citizen science, particularly triggered by these cherished plants, has been and will continue to be crucial in perfecting our knowledge of Asturian orchids.